Morsels of criticism : tending to illustrate some few passages in the Holy Scriptures upon the philosophical principles and an enlarged view of things. - King, Edward, 1735?-1807. (Tufts University. Tisch Library., 2016)
The 2nd ed. /to which is now added, by the author a 2nd and supplemental part ...; 1 online resource (3 volumes) : illustrations.; Vol. 1: xix, [3], 493 [i.e. 517], [1]; v. 2: vi, 433 [i.e 451], [1]; v. 3: xvi, 437 [i.e. 461], [43] p., [8] leaves of plates.; Vol. 1-2 have half titles: Morsels of criticism : in three volumes / by Edward King ... ; vol. 3 has half title: A second part to the morsels of criticism / by Edward King ..., vol. III.; Signatures: vol. 1: A⁸ a² b²( -b2) B⁸(B4+chi1) C-I⁸ K(K5+chi1) L-N⁸ O⁸(O5+chi1) P⁸ (P6+chi1) Q-U⁸ X⁸(X5+chi1) Y-Z⁸ 2A⁸(2A8+chi1) 2B-2D⁸ 2E⁸(2E7+chi1) 2F-2H⁸ 2I⁸( -2I8); v. 2: [A]⁸([A]8+chi1) B-C⁸ D⁸(D5+chi1) E-N⁸ O⁸(O2+chi1) P-Q⁸ R⁸(R8+chi1) S⁸ T⁸(T2,6+chi1,2) U⁸(U4+chi1) X⁸ Y⁸(Y2+chi1) Z⁸ 2A⁸(2A1+chi1) 2B-2E⁸; v. 3. A-C⁸ D⁸(D3,8+chi1,2) E⁸(E3,5+chi1,2) F⁸(F2+chi1) G-L⁸ M⁸(M5+chi1) N-P⁸ Q⁸(Q2+chi1) R-U⁸ X⁸(X5+chi1) Y-2F⁸, ²A-E⁴ ²F² [wove paper].; Additional leaves of text numerated with asterisks inserted before pages with corresponding page numbers.; Last page each vol. blank.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: ESTCt095740